Akuntabilitas Lembaga Pengelola Zakat Di Kabupaten Jember - - Yulinartati; Lely Ana Ferawati Ekaningsih; Ahmad Roziq (Conference In Business, Accounting, And Management (CBAM), 2012)
This study discusses: 1) accountability of zakat, infaq, and shodaqah adequate, 2) the usefulness of such funds to the recipient charity, infaq, and sodaqah, 3) muzaqis perception against payment and management ZIS zakat institutions. The collected data analyzed by descriptive kausalilatif. The test results perceptions of the usefulness of zakat,infaq and shodaqoh presented with statistical percentages in order to draw conclusions adequately. The study was conducted over 10 months. Zakat institutions sampled in this study, seven (7) institutions, namely: LAZISMU (Lembaga Amil, Zakat, Infak dan Shodaqoh Muhammadiyah), AZKA (Amil Zakat Al-Baitul Amien), Yatim Mandiri, LAZDEPAG (Lembaga Amil, Zakat Departemen Agama Jember), YDSF (Yayasan Dana Sosial Alfalah), BMH (Baitul Mal Hidayatullah), RIZKI (Rumah Itqon Zakat Infak). The results of this study show that: 1) Zakat Organization in Jember apply the principle of accountability which includes the following; ZIS management agency is in compliancewith applicable laws or regulations, the implementation of the fundraising is in conformity with the rules and proper procedure, the agency in distributing charity funds to mustahiq was right on target. 2) The benefits of the distribution of zakat, infaq and shadaqoh for mustahiq as follows; giving mustahiq ZIS can grow a business, can help financial sector mustahiq, could help resolve / recover mustahiq economic conditions and the provision of ZIS can encourage poor families to try to get out of the self the poverty line.Keywords: zakat, infak, shodaqoh, zakat institutions